ANALISIS PENGARUH RISIKO, TINGKAT EFISIENSI, DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN (PENDEKATAN BEBERAPA KOMPONEN METODE RISK BASED BANK RATING SEBI 13/24/DPNP/2011) - Muhamad Ibadil Mustofa; A. Mulyo Haryanto (JURNAL STUDI MANAJEMEN ORGANISASI, 2014)
Based on the phenomenon of gap that Bank of Indonesia issued new regulations on thevaluation level of banking performance using Risk Based Bank Rating Methode SEBI No.13/24/DPNP/2011 and the research gap that occured differences in the results ofresearch. This study aimed to analyze the effect of NPL (Non Performing Loan), NIM(Net Interest Margin), LDR (Loan to Deposit Ratio) ROA (Operating Expenses toOperating Income), CAR (Capital Adequacy Ratio), NOP (Net Open Position), and GoodCorporate Governance toward the level of financial performance of banks as measuredby ROA (Return on Assets)..The population that was used in this research is the Commercial Bank in Indonesia. Thesamples used were 20 commercial banks in Indonesia (period 2008-2012).Research usingpurposive sampling method for taking samples and analysis method that was used ismultiple linear regression.Based on the results of testing using multiple linear regression analysis, it can be notedthat Return On Assets influenced by NPL, NIM, LDR, BOPO, CAR, PDN, and GCG, itcan be seen from the results of the partial test (t-test), determination of coefficients test,and the simultaneous significance tests (f-test). The results showed that the variables NPL, NIM , CAR , and ROA significantly influence the level of financial performance ofbanking (ROA) but LDR , PDN , and GCG have no significant effect on the level offinancial performance of banking (ROA).Keywords: Bank Financial Performance , NPL, NIM, LDR, BOPO, CAR, PDN,GCG, ROA, RBBR